Fathers’ Views and Understandings on Promoting Creativity in Children Aged 24-36 Months: A Qualitative Study - Şakrucu , Evrim Durgut; Ata, Samet; Kışla , Şule (Primenjena psihologija, 2023)
Early childhood is a very important period for the development of children’s creativity. While mothers have been the main focus of studies investigating the role of parents in early childhood, recent studies indicate that fathers also have a major impact on their child’s development. The study aims at investigating the opinions of fathers about creativity, whether they play creativity-supporting games with their children, and their views about the role of the education system in fostering children’s creativity. A qualitative model was used in this study. The study results indicate that most fathers define creativity as associated with intelligence and believe that the education system does not support creativity. 71% of fathers reported being engaged in creative game plays with their children (e.g., puzzles, toy blocks, and unstructured games), but their concept of creative play is not very elaborate. A more knowledgeable and creativity-informed approach may be needed for fathers to be able to fully support their children’s development.